Cavernous hemangioma in adult parotid gland encroaching on the parapharyngeal space: A case report - Regmi, Manisha; Adhikari, Prabesh; Thapa, Rojin; Khadgi, Rohit (Journal of Pathology of Nepal, 2023)
Hemangiomas account for 0.4-0.6% of all tumors of the parotid gland. With about 50 cases reported worldwide in adults, diagnosing a hemangioma in the parotid gland can be difficult. An accurate diagnosis of parotid hemangiomas in adults before excision is challenging. We report a case of a 54-year-old woman with a left parotid mass of five years duration, which was rapidly increasing in size over last one year. Magnetic resonance imaging (MRI) was suggestive of a left parotid pleomorphic adenoma invading the parapharyngeal space. Fine needle aspiration cytology was inconclusive. However, with a strong clinical suspicion of a pleomorphic adenoma, left total parotidectomy was performed. The histopathological findings were of a cavernous hemangioma. The rarity of such condition in head and neck region and misdiagnosis or failing to diagnose make this case more interesting to pathologists and clinicians alike. Nevertheless, hemangioma should be considered in the differential diagnosis of parotid tumors in adults.